FENOMENA ALIH ORIENTASI PEMANFAATAN LAHAN HUTAN DI LERENG GUNUNG MURIA - Banowati, Eva (Forum Ilmu Sosial, 2009)
This study aims to identify the orientation of the phenomenon over land use on the slopes of Muria Volcano factor cause and effect and its impact. The sample includes a sample area of research Gesengan(village) and the sample of 80 respondents those determined by random technique. Research variables include education, land ownership and control, superior agricultural commodities. Ways of collecting data through interviews, surveys with questionnaires to respondents and several local leaders. Data processing in this article with Descriptive Percentage. The results showed that the educational level of respondents on average low at 6-8 years of successful education means between 6 years old (elementary school graduation) to 8 years (or class two on junior ). Citizen who have owned 4 ha or much of land just 2.50% or only 2 people, most (75%) or 60 people have land under 0.5 ha. ‘Borgan’ Mastery is over provisions of the management quota of 0.5 ha. by 31 ‘pesanggem’ or 26,25%, the largest acquisition there are 2 people or 2.25%. Cassava (manioc) is a superior commodity in the land by most ‘borgan’ or 85.25% (71 people), only 6 respondents or 7.50% that cultivating maize and cassava in one area, and 3 people that cultivating corn. Most of ‘Pesangem’ chose cassava as a crop interrupters because can giving some benefts include: 1) cassava more easily even without treatment, 2) low production costs, - 3) price stability; 4) marketable due. Cassava is the raw material for tapioca four industry that is operating around that area.Keywords: Over orientation, borgan, usefull